Refugees' integration into the Austrian labour market: Dynamics of occupational mobility and job-skills mismatch - Sandra M. Leitner; Michael Landesmann (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper analyses the employment experiences of the recent wave of Middle Eastern refugees (from Syria, Iraq, Afghanistan and Iran) in the Austrian job market. The emphasis in this research was to investigate whether refugees experienced an initial (sharp) downgrade in their occupational status when they accepted their first employment, compared with the occupation they had in their home country, and then whether (and to what extent) such a downgrade had been followed by an upgrade in the jobs they currently held. This U-shaped pattern of occupational trajectories is familiar in the migration literature, and it is here tested using data from two survey waves of recent refugees in the Austrian labour market. The paper also analyses, in its second part, subjective assessments of refugees as to whether they feel that they are 'over-' or 'under-' qualified (regarding their previous educational attainment levels and work experiences) for the jobs in which they are currently employed. In both exercises, we report results regarding the heterogeneity across groups of refugees by age, gender, their specific occupations in their home country, their educational attainment levels, their country of origin, and whether they obtained refugee status as first-time asylum applicants or through family reunion. We also refer, in the second part, to the issues of refugees' mental state and their degree of social integration with the host population.
Keywords: J15; J24; J61; J62; 330; Refugees; occupational trajectories; job-skills mismatch; Austria; refugees from Middle East; migrants' job-market integration